PENERAPAN PRINSIP NON DISKRIMINASI KAITANNYA DENGAN KETENTUAN TINGKAT KANDUNGAN DALAM NEGERI DI INDONESIA - Brazzy Upoyo, Violla; Ariananto Waluyo Adi, Emmanuel (Universitas Ekasakti, 2021)
Countries that are members of the GATT General Agreement on Tariffs and Trade (GATT), including Indonesia, have agreed to apply the principle of non-discrimination in the activities of buying and selling goods between countries. Today's modern products are owned by everyone, namely mobile phones or computers. The product is an attraction to improve the economy of a country. Indonesia, which has ratified the GATT agreement contained in Law Number 7 of 1994 concerning Ratification of the Agreement Establishing the World Trade Organization also has regulations in Law Number 25 of 2017 concerning Investment which regulates the level of domestic content for business actors from abroad who will invest in the sector of selling mobile phone and computer products so that it contradicts the agreed principle of non-discrimination. This paper uses a normative approach with analytical techniques using hermeneutic analysis and interpretation methods. The author finds that there are no laws and regulations governing the exception to the principle of non-discrimination. Keywords: Non-Discrimination, TKDN, Product